Enzymatic Clarification of Soursop Juice by Pectinase/Cellulase Enzymes Ratio - Mohamad Fuzi, Siti Fatimah Zaharah; Azman, Nur Azzyyati; A Talip, Balkis; Abdullah, Shakila (Enhanced Knowledge in Sciences and Technology, 2021)
Soursop juice clarification from enzymatic treatment of pectinase (Aspergillus aculeatus / Pectinex Ultra Clear®) and cellulase (Trichoderma reesei) ratio enzymes were studied. The enzymes were mixed in different percentage ratio of pectinase (0 – 2.0% v/w) and cellulase (0 – 2.0% v/w) formulated from simplex lattice mixture design using Design expert v.6.0.4. The absorbance of soursop juices were determined by spectrometric method. Extraction yield and viscosity of the treated juices produced were measured. The physicochemical properties including pH, total soluble solid (TSS) and total reducing sugar of the juice were determined using Lane-Eynon method. The results show that absorbance (0.77 – 0.35) and viscosity (0.09 Pa.s – 0.02 Pa.s) were significantly decreased when the enzyme mixture of 1.0 pectinase/cellulase applied. The extraction yield increased up to 60% from 30.42% (v/v) to 75.00% (v/v) for the enzyme mixture of 0.5:1.5 (pectinase:cellulase). The decreases in pH were not significant for 1.5 pectinase/0.5 cellulase enzyme mixture while TSS (16.17 ºBrix - 18.70 ºBrix) and total reducing sugar (7.44% - 10.55% increases significantly for enzyme ratio of 0.5:1.5 (pectinase:cellulase). The best enzyme mixture was found to be 0.5:1.5 (pectinase:cellulase). Based on multiple linear regression analysis, quadratic model was more significant compared to other models. This study shown improvement on the quality and yield of soursop juice while maintaining the nutritional contents compared to untreated soursop juice.